Evaluation of water life cycle in production and implementation of Autoclaved Aerated Concrete (AAC), Non-Autoclaved Aerated Concrete (NAAC), Cellular Light Weight Concrete (CLC) blocks and prioritization with multi-criteria decision systems: Case study o - Mohammad Mahdi Shahsavar; Mahdi Najafzadeh; Mehran Akrami; Reza Aghlmand; Mohammad Gheibi (Annals of Environmental Science and Toxicology - Peertechz Publications, 2021)
Due to the development of the construction industry and the rapid growth of the construction industry, the consequences of the boundless human interventions in nature and the environment gradually became apparent. In line with these efforts, the concept of sustainable development was considered by the World Commission on Environment and Development, which means meeting the needs of the present generation without compromising the ability of the next generation to meet their needs. The present study intends to evaluate water consumption in the production and implementation of three types of high-consumption and competing blocks containing Autoclaved Aerated Concrete (AAC), Non-Autoclaved Aerated Concrete (NAAC), Cellular Light Weight Concrete (CLC) in the Iranian construction industry. Case studies were conducted on well-known factories approved by Standard Company in Mashhad, water consumption in the mentioned blocks was evaluated and compared during the production and implementation process. At the end of the study, the measured values were used as raw data for multi-criteria decision analysis of the Analytic Hierarchy Process (AHP), The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), and ELimination Et Choix Traduisant la REalité (ELECTRE). The comparisons showed that the highest amount of water consumption belongs to the AAC block, and the lowest amount belongs to the CLC block. This conclusion indicates that the production of CLC block in terms of planning to conserve water resources is most in line with sustainable development policies.